HUBUNGAN ETIKA PROFESI DENGAN DISKRESI DALAM PELAKSANAAN INFORMED CONSENT DI RUMAH SAKIT - Gunawan Widjaja; Dyah Ersita Yustanti (Jurnal Kesehatan, 2025)
This study discusses the relationship between professional ethics and discretionary practices in the implementation of informed consent in hospitals using a literature review method. Informed consent is a fundamental right of patients rooted in the principles of autonomy, beneficence, and non-maleficence, and must be fulfilled by health workers in every medical action. However, in practice, healthcare professionals often face situations that require discretion, such as emergency conditions or communication limitations, forcing them to balance compliance with ethical standards and situational demands. Professional and measured discretion, while adhering to legal regulations and professional ethical codes, can provide legal protection for healthcare professionals while safeguarding patients' rights. This study emphasises the importance of a deep understanding of professional ethics, clinical communication training, and transparent documentation to ensure that discretion remains within the ethical and legal boundaries applicable in hospitals.